PERAN PERBANKAN SYARIAH DALAM MENDUKUNG UMKM PERTANIAN - YULIZAR D (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
Indonesia is an agriculture country. Fourty percent (40%) of its citizen are concentrated in this sector which has a significant contribution to the national income. However, very much challenge in this sector is waiting for a proper treatment. Critical issue in the process of developing this sector is a financial support. This paper is trying to analyse using expositional descriptive approach the agriculture sector financing opportunity that might be covered by syariah banking industry, challenges as well as its policy steps. It is found that Syariah financing scheme has a positive prospect as an alternative solution for Indonesia agriculture sector problems (i.e. financing service). To encourage and to have sound impelementation, it is expected that syariah banking industry should more courageous and innovative in delivering their financial services and doing collaborative working or channeling with Islamic microfinance institutions. On top of that, Central Bank of Indonesia as a monetary authority, might address intense support to realize such potential growth of agricultural sector.